PJMHS 2022
DOI: 10.53350/pjmhs221610147
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Burnout and its Relationship with Musculoskeletal Disorders among Healthcare College Students in Lahore, Pakistan

Abstract: Background: Burn-out is a syndrome defined as the result of chronic workplace stress that has not been successfully managed. It has three dimensions: 1) energy depletion or exhaustion 2) feelings of negativism about one's job3) reduced professional efficacy. Burn-out& musculoskeletal disorders (MSD) are the most common health problem associated with work in Europe, affecting millions of workers. Several studies have found a high prevalence of burnout among medical and dental students. Aim: To determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Concerning Pakistan, limited data is available related to Medical professionals in the emergency and gynecology department. One recent study has con rmed that medical professionals and workers who undergo burnout syndrome, also show musculoskeletal pain (31). As burnout syndrome is a result of chronic work-related stress which is resulted due to poor coping mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning Pakistan, limited data is available related to Medical professionals in the emergency and gynecology department. One recent study has con rmed that medical professionals and workers who undergo burnout syndrome, also show musculoskeletal pain (31). As burnout syndrome is a result of chronic work-related stress which is resulted due to poor coping mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Regret and guilt arise because the time was not spent doing something worthwhile. The literature on binge-watching is also inundated with its association with psychological aspects, such as depressive symptoms and impulsivity (Steins-Loeber et al, 2020), emotion (Tefertiller & Maxwell, 2018), and cognitive function (Ilyas & Qureshi, 2020). Vaterlaus et al (2019) also reported that binge-watching is used as a distraction from academic responsibilities and mental health problems and contributes to an unhealthy diet, where students consume more junk food when they binge-watch.…”
Section: Binge-watching: Conceptualisation Motivations and Consequencesmentioning
confidence: 99%
“…Since binge-watching is associated with symptoms of addiction and is influenced by various factors, it demonstrates the importance of conducting further research to understand this phenomenon. However, the majority of the available literature has looked at binge-watching using samples from university students in Australia (Horvath et al, 2017), Germany (Steinbach, 2018), the United States (Vaterlaus et al, 2019), Pakistan (Ilyas & Qureshi, 2020), Poland (Starosta et al, 2021), and Taiwan (Sun & Chang, 2021). Little research is available on samples from Malaysia, making the generalisation of past findings inappropriate for the Malaysian population as binge-watching patterns might differ across countries.…”
Section: Introductionmentioning
confidence: 99%
“…Deterioration of social relationships (Gangadharbatla et al, 2019;Dhanuka and Bohra, 2019), negative effects of the phenomena on emotional, physical and mental health (Dhanuka and Bohra, 2019), school and work (Gangadharbatla et al, 2019), daily time management, goal fulfilment, stress tolerance (Ilyas and Qureshi, 2020) and memory (Horwath et al, 2017) have all been cited as effects of BW. Some of the adverse effects of BW include, for example, tendencies towards emotional instability, intransigence, lack of perseverance , depression and impulsivity (Ahmed, 2017;Steins-Loeber et al, 2020) and regret for lost time -dependent on the degree of attention commitment during the show (Pittman and Steiner, 2019).…”
Section: Effects Of Bwmentioning
confidence: 99%